Rendering Protein-Based Particles Transiently Insoluble for Therapeutic Applications - Xu, Jing (2012)
Herein we report the fabrication of protein (bovine serum albumin, BSA) particles which were rendered transiently insoluble using a novel, reductively labile disulfide-based cross-linker. After being cross-linked, the protein particles retain their integrity in aqueous solution and dissolve preferentially under a reducing environment. Our data demonstrates that cleavage of the cross-linker leaves no chemical residue on the reactive amino group. Delivery of a self-replicating RNA was achieved via the transiently insoluble PRINT protein particles. These protein particles can provide new opportunities for drug and gene delivery.